ANALYSIS OF IMPEDANCE SPECTROSCOPY RESPONSES AND THE EFFECT OF NEODYMIUM ON GADOLINIA CERIA SOLID ELECTROLYTE BASED FOR INTERMEDIATE TEMPERATURE SOLID OXIDE FUEL CELL - Nugroho, Agung
Solid electrolyte component in Solid Oxide Fuel Cell (SOFC) is a crucial one that determine the performance of the SOFC. The main problem of this device is the high operating temperature (800-1000oC) which is determined by the electrolyte performance itself. This high temperature operation causes many practical problems and makes the devices less economical. The use of Ceria Based Electrolyte in this case Gadolinia Ceria, is an alternative solution to overcome this problem. The main objective of this research is to analyze the impedance spectroscopic responses of Gadolinia Ceria-based electrolytes system. A series of experiments were carried out starting from powder preparation, compaction, sintering process, up to impedance and physical characterizations. Variations of % Nd was conducted with the compositions of Ce0,8Gd0,15Sm0,05NdxO1,9 (x = 0%; 2,5%; 5% and 7,5%) to find the effect of Nd dopants. The results of this study indicate that the solid electrolytes produced from this research have an average grain size of ±500 nm. The equivalent electrical circuit model consists of 2 models, Rg-(Rgb/ CPEgb) and (Rg/CPEgb)-(Rgb/CPEgb). The interpretation of these model showed the transfer process at the interface of grain and grain boundaries. Variation of operating temperature in EIS testing, showed a temperature range that was a range of model changes. An increase in operating temperature leads to smaller value of impedance spectrum.. The relationship between impedance spectra with microstructure was also discussed in this thesis. The optimum % variation of Nd that is resulting the highest ionic conductivity value from this research was obtained by the electrolyte which has a 5% Nd on its compositions.